Localization of Light in Photonics Lattices for All-Optical Representation of Binaries - Nguyen, Dan T.; Nolan, Daniel A.; Borrelli, Nicholas F. (Frontiers in Physics, 2021)
In this paper we present a novel conceptual method for all optical representation of binary numbers that could be used for all-optical binary logic components in optical digital computing, as well as for other applications. The new concept is based on effect of localization of light in specially designed binary photonics lattices whose central parts resemble the represented binaries, and the localizations occur due to breaking periodicities of the lattices. The proposed structures can be made with integrated photonics on-chip that are highly programmable and controllable. Most significantly, the working principle of the novel method doesn’t require nonlinear interaction between light and material, which is the most serious obstacle in the conventional method that uses optical transistors whose mechanism relies mainly on optical nonlinearity. We will discuss some technical challenges in developing the components.